Analysis and Assessment of Lithuanian Road Accidents by AHP Method - Marius Jakimavičius (The Baltic Journal of Road and Bridge Engineering)
Lithuanian road accidents were evaluated based on the geographic information systems and multi-criteria method of Analytical Hierarchy Process This paper presents the methodology for selecting and ranking high accident concentration sections on the roads of national significance. Methodology involves the following process phases: 1) preparation of spatial data of the road accidents; 2) estimation of road sections with a high accident rate; 3) calculation of spatial statistics for estimation of accident points and hot spots; 4) selecting indicators for multi-criteria assessment; 5) calculation by Analytical Hierarchy Process method and ranking the selected high accident concentration sections. Assessment of spatial clustering of accidents and hot spots was carried out following geo-information technologies and using Getis-Ord Gi  statistics and point density functions. This geospatial criterion was integrated into multicriteria assessment for ranking the high accident concentration sections by using the Analytical Hierarchy Process method. Presented method is useful for various agencies in order to improve their planning and management strategies for better traffic conditions as well as to reduce the number of accidents. The result of the research presents selection methodology of dangerous accident section and ranking of the tenth the most dangerous sections involving geographic information systems and Analytical Hierarchy Process method.